Comparison of Efficacy of Self-Expandable Metallic Stent Placement in the Unresectable Esophageal Cancer Patients. (27th July 2017) - Uesato, Masaya; Akutsu, Yasunori; Murakami, Kentarou; Muto, Yorihiko; Kagaya, Akiko; Nakano, Akira; Aikawa, Mizuho; Tamachi, Tomohide; Arasawa, Takahiro; Amagai, Hiroyuki; Muto, Yasuhide; Matsubara, Hisahiro
Abstract : This is a retrospective study to evaluate the prevention of complications of metallic stent placement in patients with unresectable advanced esophageal cancer. A total of 87 patients were treated with 4 types of metal stents in the esophagus over a period of 18 years. Stent placement was technically successful. The most common prior treatment was chemoradiotherapy. There were no significant differences in the rate of patients with no complications among the prior treatments. Approximately, 30% of patients had the most common chest pain in complications. Stent placement within one month after the completion of chemoradiotherapy should be avoided for the prevention of the chest pain. There was no significant difference in the rate of patients with no complications by lesion location. The rate of no complications was higher for the Niti-S stent than the Gianturco Z-stent or Ultraflex stent. Of note, no complications were noted for the Niti-S ultrathin stent at all. Among cases of stent-related death, the most common type of complication was respiratory disorder caused by the stent that seems to be thick and hard. Therefore, the stent with thin and flexible characteristics like the Niti-S ultrathin stent will solve the various problems of esophageal stent placement.